2009
DOI: 10.1021/ol902510p
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Mediated Radical Nitro-Cyclization Reaction of 1,6-Dienes

Abstract: Sequential steps that involved radical addition of a nitro group to 1,6-dienes promoted by the thermal decomposition of iron nitrate(III) nonahydrate, cyclization, and trapping of the resulting terminal radicals by a chlorine atom in the presence of chloride salt afforded five-membered-ring compounds. The present reaction provides a practical method for the synthesis of nitro compounds due to its simple experimental procedure and its use of nontoxic and inexpensive iron reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 50 publications
0
27
1
Order By: Relevance
“…Disappointingly, some typical radical initiators such as Et 3 B, [9] AIBN, [10] and zinc powder [8] failed to catalyze the cyclization reaction of the allene-ene 6 a with 5 a [Eqs. (1) and (2)(3)(4)(5)], which is different from what has been previously reported. Gladly, we found that the radical addition reaction of the allene-ene 6 a with 5 a was indeed be promoted by 50 mol % of zinc powder in the presence of 20 mol % HOAc at 40 8C, thus forming two products exclusively.…”
Section: Rong Zeng Chunling Fu* and Shengming Ma*contrasting
confidence: 99%
“…Disappointingly, some typical radical initiators such as Et 3 B, [9] AIBN, [10] and zinc powder [8] failed to catalyze the cyclization reaction of the allene-ene 6 a with 5 a [Eqs. (1) and (2)(3)(4)(5)], which is different from what has been previously reported. Gladly, we found that the radical addition reaction of the allene-ene 6 a with 5 a was indeed be promoted by 50 mol % of zinc powder in the presence of 20 mol % HOAc at 40 8C, thus forming two products exclusively.…”
Section: Rong Zeng Chunling Fu* and Shengming Ma*contrasting
confidence: 99%
“…In the presence of NaN 3 , the cyclized product 4 was observed in a 25% yield, along with byproduct 5 (32%). 16 No product arising from simple addition to the alkene was observed. Additionally, both the hydroazidation and oxidation of indene using NaBD 4 were found to be non-diastereospecific (Scheme 1).…”
mentioning
confidence: 98%
“…[1] However, the radical reactions of allenes are largely unknown. [2,3] Particularly, in contrast to the radical cyclization reactions of dienes [4] and enynes, [4k-m, 5] the inter-and intramolecular tandem radical addition/cyclization reactions of allene-enes [6] has not been extensively explored. All the reported reactions proceed in an "allene-to-alkene" fashion, [6] which is consistent with the traditional notion that allenes are more reactive than alkenes towards radicals (Scheme 1).…”
mentioning
confidence: 99%